"The Role of Total Quality Management Practices In Enhancing Competitive Priorities «An Empirical Study»" - Salah, Engy; Ahmed, Mahmoud (The Arab Journal of Administration, 2022)
The study aimed to investigate the role of total quality management (customer focus - teamwork - management support - research and development - training) in enhancing the competitive priorities of companies (productivity - quality - delivery - flexibility - safety and security - employee spirit and satisfaction)Study Methodology: the study relied on the descriptive analytical approach to study the relationships between variables.Population and study sample: an empirical study was applied to Energizer Egypt to all the company's employees by distributing questionnaires and then collecting and analyzing the data using SPSS 26 program to reach the study results.The study concluded that there is a statistically significant relationship between the practices of total quality management and the competitive priorities of Energizer - Egypt.